System formations in contemporary discourse theatrical: حارث حمزة الخفاجي (Al-Academy, 2015)
System is one of the concepts that fused stages of human thought his contemplations , and the evolution of his ideas and know the universe and existence , was formed several systems and numerous multi- humanitarian field , for example : the political system , the economic system , the system of philosophical , scientific system ... etc. .The current research around trying to find the identity of the system aesthetic in general and theater in particular , the detection of compositions and how Cklath within shifts functional and conceptual , which confirms the importance of Altgria creative as characterized by the following heading towards experimentation and update ongoing , and in particular what we find in the discourse of postmodernism ,The research has included in its chapters and its subjects included several axes, the first chapter : the methodological framework and ensure that : the research problem , the importance of research and it's needed, the goals of the research, the limits of the search, and then determine the terms.Chapter II of the theoretical framework : included two sections :• The first topic: the concept of the system : between theory and procedure : The researcher tried to establish the concept of the system and then look at how to apply it and Cklath .• The second topic: formations system between monetary and theatrical speeches : The researcher went about analyzing the dimensions of morphology in the system and the most prominent theater systems in contemporary theater , such as the political system : Bertolt Brecht , philosophical system : Antonan Arto , anthropological system , the system Suri .It is then extracted researcher leading indicators theoretical framework , and the third chapter , which contained several axes including: research methodology , research sample and the method selected , the search tool , the foundations of the analysis of the research sample , sample analysis , it chose researcher intentional sample consisted regime Suri when Iraqi director ( Salah reeds ) in a play Macbeth who presented in Baghdad in 1998 , while the fourth chapter : the annexation of the conclusions and findings and research resources.